2015
DOI: 10.1007/s00442-015-3344-0
|View full text |Cite
|
Sign up to set email alerts
|

Herbivores with similar feeding modes interact through the induction of different plant responses

Abstract: Plants respond to attacks by herbivores with various defences, which are mounted through the activation of different biochemical pathways that are known to interact. Thus, the attack of a plant by one herbivore species may result in changes in the performances of other species on the same plant. It has been suggested that species with comparable feeding modes induce similar plant defences and such herbivores are therefore expected to have a negative effect on each other’s performance. We studied two closely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 57 publications
0
51
0
Order By: Relevance
“…Our results show that induction of defenses by T. urticae and prior or subsequent suppression of defenses by T. evansi roughly cancel out. Earlier, we showed that simultaneous attacks by these two spider mites also resulted in intermediate defense levels (de Oliveira et al ., ). This suggests that the induction and reduction of plant defenses by these two spider mites are, at least partially, revertible and similar biochemical pathways may be involved in the induction and reduction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results show that induction of defenses by T. urticae and prior or subsequent suppression of defenses by T. evansi roughly cancel out. Earlier, we showed that simultaneous attacks by these two spider mites also resulted in intermediate defense levels (de Oliveira et al ., ). This suggests that the induction and reduction of plant defenses by these two spider mites are, at least partially, revertible and similar biochemical pathways may be involved in the induction and reduction.…”
Section: Discussionmentioning
confidence: 97%
“…They hamper the digestion of proteins in the gut of herbivores, needed for acquiring amino acids (Ryan, ; Koiwa et al ., ). Earlier research found no clear correlation between PI activity and herbivore performance (Underwood et al ., ; da Silva et al ., ; de Oliveira et al ., ). The aim here was to further confirm this.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, such information is required for a better understanding of plant response to herbivore infestation (Nyoike and Liburd, 2013;Oliveira et al 2016). For instance, Smith and Mozingo (1983) found that even relatively small (0.1 to 11.5 per leaf) late-occurring populations of the T. urticae had measurable detrimental effects on yields and value of large-seeded Virginia-type peanuts.…”
Section: Discussionmentioning
confidence: 99%
“…These results are because of the feeding habits of peanut red mites, which inhibit photosynthesis by destroying chloroplasts with a consequent reduction in plant growth and development of nodes on the peanut main stem. Phytophagous mites belong to an important herbivorous group that is known to feed on cell contents, leading to plant stress (Lindquist et al 1996;Oliveira et al 2016). Some studies have shown that, at high levels, T. urticae infestation can suppress flowering and leaf development, affecting the quality and quantity of inflorescences produced by strawberry plants (Sances et al 1981;Fraulo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The plant defence response depends on the ability of the plant to recognize the type of herbivore that is feeding on it, that is, the nature of the feeding habit (chewing or piercing-sucking; De Moraes et al, 1998;Par e & Tumlinson, 1998), as well as the intensity of the injury (Rodriguez-Saona et al, 2010;Magalhães et al, 2018;Michereff et al, 2018). Little is known about plant defence responses to different species that feed by piercing-sucking (Delphia et al, 2007;Soler et al, 2012;de Oliveira et al, 2016). These signals include touch (Mauch et al, 1997;Hilker & Meiners, 2010), oviposition (Hilker & Meiners, 2011), volatiles such as pheromones emitted by herbivores (Magalhães et al, 2019), plant volatiles emitted by neighbouring plants (Erb et al, 2015), and elicitors present in the oral secretions of the herbivores (Hilker & Meiners, 2010;Michereff et al, 2011;Hilker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%